Answer:
3.
Step-by-step explanation:
Implicit differentiation:
x^2 y + (xy)^3 + 3x = 0
x^2 y + x^3y^3 + 3x = 0
Using the product rule:
2x* y + x^2*dy/dx + 3x^2 y^3 + x^3* (d(y^3)/dx) + 3 = 0
2xy + x^2 dy/dx + 3x^2 y^3 + x^3* 3y^2 dy/dx + 3 = 0
dy/dx(x^2 + 3y^2x^3) = (-2xy - 3x^2y^3 - 3)
dy/dx= (-2xy - 3x^2y^3 - 3) / (x^2 + 3y^2x^3)
At the point (-1, 3).
the derivative = (6 - 81 - 3)/(1 -27)
= -78/-26
= 3.
Answer:
![f^{-1}(x)=\sqrt[3]{x}-6](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D%5Csqrt%5B3%5D%7Bx%7D-6)
Step-by-step explanation:
![f(x)=(x+6)^3](https://tex.z-dn.net/?f=f%28x%29%3D%28x%2B6%29%5E3)
![y=(x+6)^3](https://tex.z-dn.net/?f=y%3D%28x%2B6%29%5E3)
![x=(y+6)^3](https://tex.z-dn.net/?f=x%3D%28y%2B6%29%5E3)
![\sqrt[3]{x}=y+6](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7Bx%7D%3Dy%2B6)
![\sqrt[3]{x}-6=y](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7Bx%7D-6%3Dy)
Answer:
16g
Step-by-step explanation:
16
16
16
16
16
16
16g
16g
16g
E = 1/2 m v^2
E = 1/2 (0.145) (40)^2
E = 0.0725 x 1600
E = 116 kg m^2/s^2
1 joule = 1 kg m^2/s^2
so here E in joules is 116 joules
so E = 116 joules
14/15
5/15 + (3x3 / 3x5) = 5/15 + 9/15 = 14/25